Keeping the books for the environment and society: The unification of emergy and financial accounting methods - Campbell, Daniel E. (Journal of Environmental Accounting and Management, 2026)
Development of the concept of emergy established a medium for accounting that made it possible to express economic and environmental work of all kinds on a common basis as solar emjoules. Environmental accounting using emdollars, a combined emergy-monetary unit, can be used to produce a single income statement and balance sheet giving comprehensive accounts for the economy, society, and the environment that can be expressed on a single income statement and balance sheet. At present, emergy accounting is rapidly developing and this paper uses well-known methods from financial accounting and bookkeeping to guide the further development of emergy accounting methods. The important concept of environmental liability is defined and a conceptual basis for applying this idea in ecologicaleconomic systems is presented in the form of an Energy Systems Language model. Four categories of environmental debt are recognized and a scheme for payment of these debts is proposed based on the criterion that economic production be sustainable. Also, a system of double entry emergy and money bookkeeping is proposed, which uses a combined emergy and money journal, separate emergy and money ledgers with this data transferred to a unified emdollar balance sheet to keep one set of books for the environment and the economy. Further development, testing, and adoption of environmental accounting tools like the ones proposed here will allow governments and managers to finally determine the true solvency (i.e., the ability to pay economic, social and environmental debts) and therefore the sustainability of the firms and economic systems for which they are responsible.